Daoism in Early China - Cao, Feng. author. aut Link
XII, 227 p.
Keywords: This text considers the prevalence of Lao-Zhuang Daoism and Huang-Lao Daoism in late pre-imperial and early imperial Chinese traditional thought. The author uses unique excavated documents and literature to explore the Huang-Lao tradition of Daoist philosophy, which exerted a great influence on China ancient philosophy and political theories, from the Pre-Qin period to the Wei-Jin periods. It explains the original and significance of Huang-Lao Daoism, its history and fundamental characteristics, notably discussing the two sides of Huang-Lao, namely the role and function of Lao Zi and the Yellow Emperor, and discusses why the two can constitute a complementary relationship. It also provides a key study of the Mawangdui silk texts, bamboo slips of the Heng Xian, Fan Wu Liu Xing, considering both the theory of human Xing and of Qi.